Normative centre of pressure values for single leg standing and tandem stance in children between the ages of six and ten years : a pilot study - Nevin, Michaela (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScPhysio)--Stellenbosch University, 2016.